Implementation of Religious Activities in Developing Religious Character and Social Responsibility of Students at Raudhatul Athfal Adz-Dzikra Isyhaarul Jannah School in Tiumang Sub-District, Dharmasraya Regency - Evi Suryaningrum; Sayfiq Amir (Yayasan Adra Karima Hubbi, 2025)
In the era of globalization, the massive influence of foreign culture and technology threatens to strengthen religious values and social awareness in early childhood (Borolla & Marini, 2022; Munawir et al., 2023). Raudhatul Athfal (RA) schools as Islamic educational institutions have a strategic role in shaping religious character and social responsibility, but many schools still separate religious practices from the development of social care (Kemenag Dharmasraya, 2023). This study aims to analyze the implementation of religious activities at RA Adz-Dzikra Isyhaarul Jannah in developing the religious character and social responsibility of students, as well as identifying the supporting and inhibiting factors. This research uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and document studies. The research subjects included teachers, students, and parents at RA Adz-Dzikra Isyhaarul Jannah, Dharmasraya. The data were thematically analyzed to identify the implementation patterns of religious activities and their impact on character building. The results show that this school implements seven main activities: Tadarus Al-Qur'an, Dhuha Prayer, Dhikr and Prayer, Tahfidz, Hadith Memorization, Arabic Language Learning, and Friday Infaq.